Pengembangan Sumber Belajar Berbasis Pembuatan Edible Film dari Pati Biji Durian pada Materi Polimer - Rismayanti Octavia; yuni fatisa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
AbstractPolymer is one of Chemistry materials that wasvery closely related in the daily life, but a learning resource on that material at Senior High School is limited. Thus, a learning resource contextual based such video is needed to be developed.This research aimed at developing a valid and practical learning resource such video based onpreparing edible film of durian seed starch with the addition of basil leave extract and knowing chemistry and physic characteristics of edible film.This research was a Research and Development (R&D) with 4D (four-D) model, modified by doing limited trialsand removing disseminating step. In the Design step, laboratory research plan of preparing edible film of durian seed starch with the addition of basil leave extract. Based on the validity test, developing video was stated on valid category with 74.33% percentage of validity level. Based on the practicality test, developing video was stated on very practicalcategory with 82% percentage of practicality level. The best edible film was on 2 graddition of basil leave extract, physic characteristic ofwater vapor transmission rate was 3.401361 g/m2.24 hours, chemistry characteristic of water content was 14% on edible film withoutthe addition of basil leave extract, and the strongest antioxidant activity was 3.4366 µg/mL onediblefilm with 2 graddition of basil leave extract.Keywords: Learning Resource, Edible Film, Polymer